Perovskite cell packaging coating, perovskite cell and preparation method

By spraying a mixture of polyurethane and CdSe quantum dots on the second electrode of the perovskite cell, a stable functional material layer is formed, which solves the problem of poor stability of perovskite photovoltaic modules in practical applications, achieves higher photothermal stability and water vapor stability, and extends the service life of the module.

CN119570346APending Publication Date: 2025-03-07TRINA SOLAR CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411677194.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

In practical applications, perovskite photovoltaic modules have poor stability of light, heat and water vapor, resulting in energy loss and performance degradation, and have not yet reached the same level of stability and reliability as traditional crystalline silicon photovoltaic modules.

Method used

Using a mixture formed by polyurethane and CdSe quantum dots as the encapsulation coating, a stable functional material layer is formed on the second electrode of the perovskite cell by spraying and annealing processes to effectively encapsulate water vapor and manage the absorption of ultraviolet light.

Benefits of technology

It significantly improves the photothermal stability and water vapor stability of perovskite batteries, extends the service life of the components, and improves its reliability and long-term power stability in practical applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570346A_ABST
    Figure CN119570346A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of perovskite batteries, and particularly provides a packaging coating of a perovskite battery, the perovskite battery and a preparation method. The invention discloses a packaging coating of a perovskite battery. The packaging coating comprises polyurethane and CdSe quantum dots. And the mixture formed by the two can effectively package water vapor and prevent the water vapor from permeating into the photovoltaic module, so that the performance reduction or damage of the module caused by the water vapor is avoided. In addition, the CdSe quantum dots can convert part of ultraviolet light energy into light with visible wavelength under the irradiation of ultraviolet light, and the process is beneficial to improving the light absorption efficiency of the photovoltaic module. In addition, the mixture of the polyurethane and the CdSe quantum dots can effectively control the absorbed heat energy on the surface of the photovoltaic module, so that the heat energy can be quickly released, and the temperature of the photovoltaic module is further reduced. The temperature reduction not only helps to improve the photoelectric conversion efficiency of the photovoltaic module, but also can enhance the long-term operation stability of the photovoltaic module.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of perovskite cells, and specifically provides a packaging coating of a perovskite cell, a perovskite cell and a preparation method thereof. Background Art

[0002] With the increasing global awareness of environmental protection and the rising demand for clean energy, photovoltaic power generation, as a renewable and clean form of energy, has received widespread attention and attention worldwide. Among the many photovoltaic technologies, perovskite technology has become one of the most eye-catching products in the photovoltaic field after 10 years of development. In recent years, with the continuous improvement of the quality of perovskite materials and related technologies, the efficiency of perovskite cells has been significantly improved, and the efficiency of a single cell has exceeded 26%. However, in actual operation, perovskite photovoltaic modules often face the problem of poor light, heat and water vapor stability. These problems will cause energy loss and performance degradation in perovskite photovoltaic modules in actual applications, so that they have not yet reached the same level of stability and reliability as traditional crystalline silicon photovoltaic modules.

[0003] Therefore, how to effectively solve the stability problem of perovskite battery components in practical applications has become a key technical barrier to whether perovskite photovoltaic technology can achieve large-scale industrialization and commercial application. Summary of the invention

[0004] In order to overcome the above-mentioned defects, the present invention provides a packaging coating for a perovskite cell, a perovskite cell and a preparation method, which improves the photothermal stability and water vapor stability of the perovskite cell by managing the absorption of ultraviolet light by the packaging coating.

[0005] In a first aspect, the present invention provides an encapsulation coating for a perovskite cell, comprising: polyurethane and CdSe quantum dots.

[0006] Furthermore, the volume ratio of the polyurethane to the CdSe quantum dots is (50-200):1.

[0007] The volume ratio of the polyurethane to the CdSe quantum dots is 100:1.

[0008] Furthermore, the molecular weight of the polyurethane is 1000-5000.

[0009] In a second aspect, the present invention provides a perovskite battery, comprising:

[0010] substrate;

[0011] A first electrode formed on the substrate;

[0012] a first transmission layer formed on the first electrode;

[0013] a perovskite layer formed on the first transmission layer;

[0014] a second transport layer formed on the perovskite layer;

[0015] The second electrode is formed on the second transmission layer.

[0016] The coating layer according to the first aspect is formed on the second electrode.

[0017] Furthermore, the first transport layer is a hole transport layer, and the second transport layer is an electron transport layer.

[0018] In a third aspect, the present invention provides a method for preparing a perovskite battery, comprising:

[0019] forming a first electrode on a substrate;

[0020] forming a first transmission layer on the first electrode;

[0021] forming a perovskite layer on the first transport layer;

[0022] forming a second electrode on the perovskite layer;

[0023] The coating layer described in the first aspect is formed on the second electrode.

[0024] Further, forming the coating on the second electrode comprises:

[0025] Weigh polyurethane and CdSe quantum dots according to a preset ratio;

[0026] preparing a polyurethane aqueous solution;

[0027] dispersing CdSe quantum dots in the polyurethane aqueous solution to form a mixed solution;

[0028] spraying the mixed solution onto the second electrode;

[0029] Anneal at a preset temperature.

[0030] Furthermore, the solid content of the aqueous polyurethane dispersion system is 1%-5%.

[0031] Further, spraying the mixed solution on the second electrode comprises:

[0032] The mixed solution is sprayed on the second electrode at 70-100°C.

[0033] Further, the annealing at a preset temperature includes:

[0034] Anneal at 100-120°C for 15-25 minutes.

[0035] The above one or more technical solutions of the present invention have at least one or more of the following beneficial effects:

[0036] In the technical solution of the present invention, a mixture of polyurethane and CdSe quantum dots is used to prepare an encapsulation coating, which can effectively encapsulate water vapor and prevent water vapor from penetrating into the interior of the perovskite cell photovoltaic module, thereby avoiding performance degradation or damage of the module caused by water vapor.

[0037] In addition, CdSe quantum dots can convert part of the ultraviolet light energy into visible wavelength light under ultraviolet light irradiation, and this process helps to improve the light absorption efficiency of photovoltaic modules. In addition, the mixture of polyurethane and CdSe quantum dots can effectively control the absorbed heat energy on the surface of photovoltaic modules, which is conducive to the rapid release of heat energy and further reduces the temperature of photovoltaic modules. Lowering the temperature not only helps to improve the photoelectric conversion efficiency of photovoltaic modules, but also enhances their long-term operation stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] The disclosure of the present invention will become more easily understood with reference to the accompanying drawings. It is easy for those skilled in the art to understand that these drawings are only for illustrative purposes and are not intended to limit the scope of protection of the present invention. In addition, similar numbers in the figures are used to represent similar components, among which:

[0039] Figure 1 is a schematic diagram of the main structural block diagram of a perovskite battery according to an embodiment of the present invention;

[0040] Figure 2 is a schematic diagram of the main steps of a method for preparing a perovskite battery according to an embodiment of the present invention;

[0041] Figure 3 It is a schematic diagram comparing the EQE curves of the perovskite cells obtained according to Comparative Example 1 and Example 2 of the present invention.

[0042] Reference numerals list :

[0043] 1: substrate; 2: first electrode; 3: first transport layer; 4: perovskite layer; 5: second transport layer; 6: second electrode; 7: coating. DETAILED DESCRIPTION

[0044] Some embodiments of the present invention are described below with reference to the accompanying drawings. It should be understood by those skilled in the art that these embodiments are only used to explain the technical principles of the present invention and are not intended to limit the protection scope of the present invention.

[0045] The invention provides a packaging coating for a perovskite battery, comprising polyurethane and CdSe quantum dots.

[0046] Quantum dots are semiconductor nanostructures that bind excitons in three spatial directions. Quantum dots are nanoscale semiconductors. By applying a certain electric field or light pressure to this nano-semiconductor material, they will emit light of a specific frequency, and the frequency of the emitted light will change with the change of the size of the semiconductor. Therefore, by adjusting the size of the nano-semiconductor, the color of the light it emits can be controlled. Cadmium selenide (CdSe) quantum dots are nanoparticles composed of Cd and Se elements. CdSe quantum dots have adjustable optical properties, and their absorption and emission spectra can be achieved by adjusting their size. They show good optical properties in the ultraviolet to visible spectrum range, with excellent fluorescence quantum yield and narrow emission bandwidth.

[0047] Polyurethane (PU), whose full name is polyurethane, has good heat insulation, sound insulation, shock resistance and anti-toxic properties.

[0048] The present invention creatively combines polyurethane materials with CdSe quantum dots to develop a new type of coating material, which is particularly suitable for the encapsulation of perovskite materials. Through the application of this coating, its integration can be achieved during the production and processing of the battery, thereby bringing multiple advantages. First, this coating can help form a high-quality film, which is crucial to the performance of the perovskite material. Secondly, the coating can optimize the light absorption spectrum of the perovskite material, making it more efficient in absorbing light energy, thereby improving the energy conversion efficiency of the battery. In addition, this coating also has excellent water-blocking properties and can effectively block the erosion of external water vapor, which is of great significance for extending the service life of the perovskite solar cell module. Through these improvements, the long-term power stability of the perovskite solar cell module is significantly improved, so that it exhibits more excellent performance and reliability in practical applications.

[0049] In one embodiment, the volume ratio of polyurethane and CdSe quantum dots is set to (50-200): 1. By precisely controlling the mixing ratio of the two materials, it is possible to ensure that polyurethane and CdSe quantum dots are mixed in a specific ratio, thereby achieving a series of important functions. First, the mixture formed by the two can effectively encapsulate water vapor and prevent water vapor from penetrating into the interior of the photovoltaic module, thereby avoiding the degradation or damage of the module performance caused by water vapor. In addition, CdSe quantum dots can convert part of the ultraviolet light energy into light of visible wavelengths under ultraviolet light irradiation. This process helps to improve the light absorption efficiency of the photovoltaic module. In addition, the mixture of polyurethane and CdSe quantum dots can also effectively control the absorbed heat energy on the surface of the photovoltaic module, which is conducive to the rapid release of heat energy and further reduces the temperature of the photovoltaic module. Lowering the temperature not only helps to improve the photoelectric conversion efficiency of the photovoltaic module, but also enhances its long-term operation stability.

[0050] In a specific embodiment, the volume ratio of the polyurethane to the CdSe quantum dots is 100:1.

[0051] In one embodiment, the molecular weight of the polyurethane is 1000-5000.

[0052] Reference Figure 1 The present invention provides a perovskite cell, comprising, from bottom to top, a substrate 1, a first electrode 2, a first transmission layer 3, a perovskite layer 4, a second transmission layer 5, a second electrode 6 and a coating 7.

[0053] The first electrode 2 is formed on the substrate 1. The first electrode 2 is usually made of conductive metal such as gold (Au) or silver (Ag), and is used to collect holes transmitted from the hole transport layer.

[0054] The first transmission layer 3 is formed on the first electrode 1 .

[0055] The perovskite layer 4 is formed on the first transmission layer 3; the perovskite layer 4 is made of a perovskite material (such as CH 3 NH 3 PbI 3 ) is responsible for absorbing sunlight and generating photogenerated electron-hole pairs.

[0056] The second transmission layer 5 is formed on the perovskite layer 4 .

[0057] The second electrode 6 is formed on the second transmission layer 5. The second electrode 6 is made of a transparent conductive substrate, usually fluorine-doped tin oxide (FTO) or indium-doped tin oxide (ITO), and mainly acts as an electrode for collecting photocurrent.

[0058] The coating layer 7 is formed on the second electrode 6 .

[0059] Furthermore, the first transport layer 3 is a hole transport layer for transporting holes and blocking electrons. The hole transport layer is usually composed of an organic material (such as spiro-OmetaD) or an inorganic material (such as CuSCN).

[0060] The second transport layer 5 is an electron transport layer, which mainly transports photogenerated electrons and blocks holes. This layer is usually made of titanium dioxide (TiO 2 ) or other metal oxides. The electron transport layer should have a high electron mobility, and its conduction band minimum value is lower than the conduction band minimum value of the perovskite material, so as to receive the electrons transmitted by the perovskite layer and transmit them to the transparent conductive substrate.

[0061] In the actual operation of the perovskite cell of the present invention, when light penetrates the special coating on its surface, the energy of ultraviolet light can be effectively reduced to the wavelength range of visible light. This process not only ensures that light in other bands can be effectively absorbed by the cell, but also controls the generated heat energy on the surface of the cell, which is conducive to the rapid release of heat energy. This design significantly reduces the temperature of the photovoltaic module, thereby improving the photoelectric conversion efficiency and overall stability of the cell.

[0062] Specifically, when light is incident from one side of the transparent conductive substrate, it first passes through this special coating, then continues to penetrate the electron transport layer, and finally reaches the perovskite light absorption layer. In the perovskite layer, the absorbed light energy excites the generation of electron-hole pairs. These electrons are then effectively collected by the electron transport layer and transported to the transparent conductive substrate, while the holes reach the metal electrode through the hole transport layer. This process ultimately forms a photocurrent, thereby achieving photoelectric conversion.

[0063] Before the light is incident on the electron transport layer, the coating in the present invention has reduced the energy of the ultraviolet light to the visible wavelength, while ensuring that the light energy in other bands is effectively absorbed. In addition, the coating also has the function of controlling the heat energy on the surface of the battery, which is not only conducive to the release of heat energy, but also further reduces the temperature of the photovoltaic module, thereby improving the photoelectric conversion efficiency and the stability of the battery. It is worth mentioning that the coating of the present invention also has the function of encapsulating water vapor, which further improves the stability and durability of the battery. Through this design, the battery can better resist the influence of the external environment, extend its service life, and ensure that a high photoelectric conversion efficiency can be maintained under various conditions.

[0064] The present invention also provides a method for preparing a perovskite battery, referring to Figure 2 ,include:

[0065] S1, forming a first electrode on a substrate.

[0066] S2, forming a first transmission layer on the first electrode.

[0067] S3, forming a perovskite layer on the first transport layer;

[0068] S4, forming a second electrode on the perovskite layer.

[0069] S5, forming a coating layer on the second electrode.

[0070] In one embodiment, step S5, forming the coating on the second electrode comprises:

[0071] S51, weighing polyurethane and CdSe quantum dots according to a preset ratio. The CdSe quantum dots can be obtained through commercial purchase.

[0072] S52, preparing a polyurethane aqueous solution.

[0073] S53, dispersing CdSe quantum dots in the polyurethane aqueous solution to form a mixed solution.

[0074] S54, spraying the mixed solution onto the second electrode;

[0075] S55, annealing at a preset temperature.

[0076] In one embodiment, the concentration of the polyurethane aqueous solution is 1%-5% of the solid content of the aqueous polyurethane dispersion system.

[0077] In one embodiment, in step S54, spraying the mixed solution on the second electrode includes:

[0078] S541, depositing the mixed solution uniformly on the second electrode by spraying at 70-100°C. The spraying is performed on a hot stage, and the temperature of the hot stage is set at 70-100°C.

[0079] In one embodiment, in step S55, the annealing at a preset temperature includes:

[0080] Anneal at 100-120°C for 15-25 minutes.

[0081] In one embodiment, the mixed solution formed in step S53 is stored at 5-15 degrees Celsius for future use.

[0082] In one embodiment, in step S54, the spraying rate is 3-5 nm / cycle, for a total of 5-10 cycles.

[0083] Through the process method of the present invention, an innovative functional coating process is introduced in the manufacturing process of perovskite components. Specifically, after completing the printing or deposition step of the electrode, a layer of specific functional material is added. Subsequently, by performing an annealing process, a stable functional material layer can be effectively formed. The reason why this functional material layer has significant advantages is that it contains ultraviolet fluorescent nanomaterials such as CdSe quantum dots. The presence of these nanomaterials significantly improves the photoelectric conversion efficiency of the perovskite cell and enhances its overall stability. In this way, the perovskite cell is not only improved in performance, but also shows higher reliability during long-term use.

[0084] The perovskite cell is prepared by the method of the present invention.

[0085] Example 1

[0086] CdSe quantum dots and polyurethane are obtained through commercial procurement. The molecular weight of the purchased polyurethane is 1000-5000.

[0087] Weigh the CdSe quantum dots and polyurethane accurately in a volume ratio of 1:100. Make sure that the weighed amounts of CdSe quantum dots and polyurethane meet this ratio to ensure the accuracy of subsequent experiments. When preparing an aqueous polyurethane dispersion, ensure that its solid content is between 1% and 5%. Disperse the weighed CdSe quantum dots evenly in the prepared polyurethane aqueous solution to ensure that the quantum dots are evenly distributed in the solution without agglomeration. This goal can be effectively achieved through sufficient stirring and ultrasonic treatment. The prepared mixture needs to be stored in an environment of 5 to 15 degrees Celsius to maintain its stability and effectiveness.

[0088] According to the conventional perovskite battery manufacturing process, the first electrode, the first transport layer, the perovskite layer and the second electrode are first formed on the substrate in sequence. Then, the previously saved mixed solution is evenly coated on the surface of the second electrode by spraying or scraping technology. During the spraying process, the spraying rate is controlled at 4 nanometers per cycle, each spraying is a cycle, and each time the spraying is performed, the amount of mixed solution sprayed on the surface of the second electrode is 3-5nm. A total of 9 cycles are performed. Through this method of multiple spraying in batches, the uniformity of the spraying can be effectively guaranteed, and the problem of uneven coating or uneven thickness can be avoided. In addition, the spraying operation is carried out on a hot table with a set temperature of 80°C. This temperature setting is to ensure that the coating can be properly dried during the spraying process, so as to obtain better adhesion and uniformity.

[0089] After spraying, the coating is placed in a continuous high temperature environment on the hot stage. Over time, the coating gradually dries and forms a uniform and stable film layer. In order to further improve the quality and stability of the coating, the next step is to place the sample in an environment with a temperature of 110°C for annealing. In this process, the annealing time is set to 20 minutes to ensure that the coating can be fully heat treated to achieve the best performance. After this series of processing steps, the final coating exhibits stable and uniform characteristics, which provides good protection for the performance of perovskite cells and ensures the reliability and durability of the cells in practical applications.

[0090] Example 2

[0091] CdSe quantum dots and polyurethane are obtained through commercial procurement. The molecular weight of the purchased polyurethane is 1000-5000.

[0092] Weigh accurately according to the volume ratio of CdSe quantum dots and polyurethane of 1:50. Make sure the weighed amount of CdSe quantum dots and polyurethane meets this ratio to ensure the accuracy of subsequent experiments. When preparing the water-based polyurethane dispersion system, ensure that its solid content is between 1% and 5%.

[0093] The weighed CdSe quantum dots are evenly dispersed in the prepared polyurethane aqueous solution to ensure that the quantum dots are evenly distributed in the solution without agglomeration. This goal can be effectively achieved through sufficient stirring and ultrasonic treatment. The prepared mixture needs to be stored in an environment of 5 to 15 degrees Celsius to maintain its stability and effectiveness.

[0094] According to the conventional perovskite cell process, the first electrode, the first transport layer, the perovskite layer and the second electrode are formed on the substrate in sequence. The previously saved mixed solution is evenly coated on the surface of the second electrode by spraying technology. During the spraying process, the spraying rate is controlled at 5 nanometers per cycle, and a total of 5 cycles are performed. The spraying operation is carried out on a hot stage set at 70°C.

[0095] After spraying, the coating gradually dries under the continuous heat of the hot stage, forming a uniform and stable film layer. In order to further improve the quality and stability of the coating, the sample is then placed at 100°C for annealing, and the annealing time is set to 25 minutes. After this series of processing steps, the final coating exhibits stable and uniform characteristics.

[0096] Example 3

[0097] CdSe quantum dots and polyurethane are obtained through commercial procurement. The molecular weight of the purchased polyurethane is 1000-5000.

[0098] Weigh the CdSe quantum dots and polyurethane accurately in a volume ratio of 1:200. Make sure that the weighed amounts of CdSe quantum dots and polyurethane meet this ratio to ensure the accuracy of subsequent experiments. When preparing an aqueous polyurethane dispersion, ensure that its solid content is between 1% and 5%. Disperse the weighed CdSe quantum dots evenly in the prepared polyurethane aqueous solution to ensure that the quantum dots are evenly distributed in the solution without agglomeration. This goal can be effectively achieved through sufficient stirring and ultrasonic treatment. The prepared mixture needs to be stored in an environment of 5 to 15 degrees Celsius to maintain its stability and effectiveness.

[0099] According to the conventional perovskite cell process, the first electrode, the first transport layer, the perovskite layer and the second electrode are formed on the substrate in sequence. The previously saved mixed solution is evenly coated on the surface of the second electrode by spraying technology. During the spraying process, the spraying rate is controlled at 3 nanometers per cycle, and a total of 10 cycles are performed. The spraying operation is carried out on a hot stage set at a temperature of 100°C.

[0100] After spraying, the coating gradually dries under the continuous heat of the hot stage, forming a uniform and stable film layer. In order to further improve the quality and stability of the coating, the sample is then placed at 120°C for annealing, and the annealing time is set to 15 minutes. After this series of processing steps, the final coating exhibits stable and uniform characteristics.

[0101] Comparative Example 1

[0102] The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 adopts a conventional perovskite cell manufacturing process, and the specific steps are as follows: first, a first electrode is deposited on a substrate in sequence, then a first transmission layer is formed thereon, then a perovskite layer is formed on the first transmission layer, and finally a second electrode is formed on the perovskite layer. After the second electrode is formed, no additional coating is sprayed on the second electrode in Comparative Example 1.

[0103] The perovskite cells prepared in Examples 1-3 and Comparative Example 1 were subjected to electrochemical tests, and the test results are shown in Table 1.

[0104] Table 1 Electrochemical test results of the embodiments and comparative examples

[0105]

[0106] It can be seen from the experimental data in Table 1 that the perovskite battery sprayed with the coating of the present invention can effectively improve the electrochemical performance. Taking Example 1 as an example, the specific analysis is as follows:

[0107] Photovoltaic conversion efficiency (PCE) is one of the important indicators for measuring the performance of solar cells. It indicates the ability of solar cells to convert light energy into electrical energy. The photovoltaic conversion efficiency (PCE) of the present invention is significantly better than that of the comparative example. This shows that the energy conversion efficiency of the perovskite cell coated with the coating of the present invention is higher. High PCE means less energy loss during the conversion process, which improves energy utilization efficiency.

[0108] By measuring the JV characteristic curve of the perovskite solar cell, a series of key parameters can be obtained, such as the open circuit voltage (VOC), short circuit current density (JSC) and fill factor (FF) in Table 1. These parameters are of great significance for evaluating the performance of perovskite solar cells. The open circuit voltage (VOC) of the embodiment of the present invention is slightly higher than that of the comparative example: it means that the terminal voltage of the battery is high in the open circuit state, which usually means that the potential difference between the positive and negative electrodes of the battery is large, the energy conversion capability of the battery is strong, and the non-radiative recombination loss is small, which is conducive to improving the overall efficiency of the battery.

[0109] The short-circuit current density (JSC) of the embodiment of the present invention is significantly improved compared with the comparative example, indicating that under short-circuit conditions, the current passing through the battery per unit area is larger, which reflects the effective use of light and high charge transfer efficiency of the battery, which is beneficial to improving the power output of the battery.

[0110] The fill factor (FF) of the embodiment of the present invention is slightly lower than that of the comparative example, but the reduction in GAP% is only -0.01%, which will not have a significant impact on the battery performance.

[0111] Overall, by analyzing and comparing the test results in Table 1, it can be seen that the perovskite batteries of Example 1, Example 2 and Example 3 have advantages in electrochemical performance, especially Example 1 has significant advantages. These results provide an important reference for further optimizing the preparation process of perovskite batteries and improving their electrochemical performance.

[0112] From the experimental data shown in Table 1, it can be found that the perovskite cells sprayed with the coating involved in the present invention have been significantly improved in electrochemical performance. Figure 3 A comparison of the external quantum efficiency (EQE) curves of the perovskite cells prepared in Comparative Example 1 and Example 2 is also presented. From this figure, it can be intuitively seen that the responsivity of the perovskite cell in Example 2 in the short-wave band of 300-500 nanometers is relatively low, but the responsivity in the medium-wave band of 500-700 nanometers is significantly improved. This shows that the coating provided by the present invention has a significant effect of effectively converting light energy in the short-wave band into light energy in the 500-700 nanometer band.

[0113] The present invention not only performs well in improving the electrochemical performance of perovskite cells, but also can significantly enhance the packaging effect of perovskite cells. Through the application of this coating, the stability and durability of perovskite cells are further guaranteed, thus providing more reliable guarantees for practical applications.

[0114] It should be pointed out that although the various steps in the above embodiments are described in a specific order, those skilled in the art can understand that in order to achieve the effects of the present invention, different steps do not have to be performed in such an order. They can be performed simultaneously (in parallel) or in other orders. These changes are within the scope of protection of the present invention.

[0115] So far, the technical solutions of the present invention have been described in conjunction with the preferred embodiments shown in the accompanying drawings. However, it is easy for those skilled in the art to understand that the protection scope of the present invention is obviously not limited to these specific embodiments. Without departing from the principle of the present invention, those skilled in the art can make equivalent changes or substitutions to the relevant technical features, and the technical solutions after these changes or substitutions will fall within the protection scope of the present invention.

Claims

1. A packaging coating for a perovskite battery, characterized in that: include: Polyurethane and CdSe quantum dots.

2. The coating according to claim 1, characterized in that The volume ratio of the polyurethane to the CdSe quantum dots is (50-200):

1.

3. The coating according to claim 2, characterized in that The volume ratio of the polyurethane to the CdSe quantum dots is 100:

1.

4. The coating according to claim 1, characterized in that The molecular weight of the polyurethane is 1000-5000.

5. A perovskite battery, characterized in that: include: substrate; A first electrode formed on the substrate; a first transmission layer formed on the first electrode; a perovskite layer formed on the first transmission layer; a second transport layer formed on the perovskite layer; The second electrode is formed on the second transmission layer. The coating according to any one of claims 1 to 4, formed on the second electrode.

6. A method for preparing a perovskite battery, characterized in that: include: forming a first electrode on a substrate; forming a first transmission layer on the first electrode; forming a perovskite layer on the first transport layer; forming a second electrode on the perovskite layer; The coating according to any one of claims 1 to 4 is formed on the second electrode.

7. The method according to claim 6, characterized in that The forming of the coating on the second electrode comprises: Weigh polyurethane and CdSe quantum dots according to a preset ratio; preparing a polyurethane aqueous solution; dispersing CdSe quantum dots in the polyurethane aqueous solution to form a mixed solution; spraying the mixed solution onto the second electrode; Anneal at a preset temperature.

8. The method according to claim 7, characterized in that The solid content of the aqueous polyurethane dispersion system is 1%-5%.

9. The method according to claim 7, characterized in that: The step of spraying the mixed solution onto the second electrode comprises: The mixed solution is sprayed on the second electrode at 70-100°C.

10. The method according to claim 7, characterized in that The annealing at a preset temperature includes: Anneal at 100-120°C for 15-25 minutes.

Citation Information

Patent Citations

  • Application of barrier membrane with light conversion function in photovoltaic cell laying structure

    CN109795177A

  • Curved-surface battery and packaging method thereof

    CN114695665A

  • Method of recovering valuable metal including lithium from waste lithium battery

    KR1020210131258A

  • Individually encapsulated solar cells and solar cell strings having a substantially inorganic protective layer

    US20070295390A1